(untitled) (Jurnal Bina Praja, 2022)
Crisis, natural or man-made, is inevitable in our life because of human social interactions. Crises are caused by ineffective communication yet are better solved with effective communication. Scholars have studied social media’s role in crisis management as an information propagator and their cost effectiveness during a crisis. Social media can potentially influence multiple public strata during and after the crisis. Social media serve as tools for relationship management which is a crucial part of crisis management; equally, public relations also serve the same. This paper explores how effective crisis communication management can be achieved via Social Networking Systems (SNS). Drawing from the existing literature as the method used, this paper reviews articles and studies on public relations strategy and effective crisis management. It expounds on examples of how relationships can be well-managed through social media in crises. This paper has increased our knowledge of crisis management by understanding how crises are managed. Findings are that crisis communication was managed from four conceptual lenses scholars have investigated; that crises can be prevented- partially if not completely- with a proper crisis communication plan; that having a crisis communication plan may not suffice except is handled by professional relationship managers who know how to communicate and understand the use of the conventional and new media with the influential role of symmetrical communication. Therefore, the paper concluded that since crisis leads to the bad relationship due to a lack of understanding of the situation and behavior and to facilitate this, it suggests that crisis is better managed through effective public relations managers.